Strategic delegation, quality competition, and new product profitability. Issue 3 (20th April 2015) - Shin, Hyun; Shin, Jongtae; Yoo, Shijin; Song, Joon; Kim, Alex
Abstract : Purpose: – The purpose of this paper is to present a new perspective on the marketing-R & D interface by modelling firms that develop new products in a duopolistic market. Design/methodology/approach: – By using a game-theoretic modelling approach, this study examines strategic delegation, through which the marketing and R & D managers of each firm are given authority over pricing and new products' quality levels. Findings: – Interestingly, the study finds that the case where two managers with conflicting incentives negotiate (the horizontal coordination case) might produce a better financial outcome than when the managers' decisions are perfectly coordinated by a profit-maximizing CEO (the vertical control case). In addition, the study identifies several conditions that guarantee horizontal coordination's generation of higher profit, such as high (or low) sensitivity to the quality (or price) of a new product. The paper further shows that two competing firms may select horizontal coordination as a Nash equilibrium. Practical implications: – These findings provide new insights into the role of marketing-R & D interaction under strategic delegation, which may allow rival firms to "spend smart" on R & D, avoid excessive (and unnecessary) quality competition, and thus enhance the profitability of new products. Such insights would be useful for any firms under budget constraints. Originality/value: – To the authors' knowledge, this paper represents the first attempt to analyze how delegation interacts with the conflicting incentives of marketing and R & D managers, which in turn affects the quality investment decisions, competitive intensity, and, ultimately, the financial outcomes of new products developed competing firms.